Sejarah DPRD Sumatera Selatan Masa Orde Baru - Dedi Irwanto (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this study is to analyze the development of learning media Infographics on local history of South Sumatra DPRD material during the New Order period with a valid, effective problem-based learning model and knowing the increase in student learning activity towards local history material of the South Sumatra DPRD during the New Order period. The validity of learning media is based on the validation results of three expert experts, namely material experts, grammar experts and media experts. In material validation, the score obtained was 4.80, media validation was 4.75 and grammar validation was 4.80 with very valid categories. Then, the learning outcomes of students increased by 43% with an N-gain value of 0.95 with a very effective category. So this shows that the learning media infographic local history of the South Sumatra DPRD material during the New Order period with a problem-based learning model is valid, effective and can increase the learning activity of class XII IPS 1 students